Immunopathological Changes in SARS-CoV-2 Critical and Non-critical Pneumonia Patients: A Systematic Review to Determine the Cause of Co-infection - Samadder, Saikat (Frontiers in Public Health, 2021)
The ongoing COVID-19 pandemic originating from Wuhan, China is causing major fatalities across the world. Viral pneumonia is commonly observed in COVID-19 pandemic. The number of deaths caused by viral pneumonia is mainly due to secondary bacterial or fungal infection. The immunopathology of SARS-CoV-2 viral pneumonia is poorly understood with reference to human clinical data collected from patients infected by virus and secondary bacterial or fungal infection occurring simultaneously. The co-infection inside the lungs caused by pneumonia has direct impact on the changing lymphocyte and neutrophil counts. Understanding the attribution of these two immunological cells triggered by cytokines level change is of great importance to identify the progression of pneumonia from non-severe to severe state in hospitalized patients. This review elaborates the cytokines imbalance observed in SARS-CoV-1 (2003 epidemic), SARS-CoV-2 (2019 pandemic) viral pneumonia and community acquired pneumonia (CAP) respectively in patients to determine the potential reason of co-infection. In this review the epidemiology, virology, clinical symptoms and immunopathology of SARS-CoV-2 pneumonia are narrated. The immune activation during SARS-CoV-1 pneumonia, bacterial and fungal pneumonia is discussed. Here it is further analyzed with the available literatures to predict the potential internal medicines, prognosis and monitoring suggesting better treatment strategy for SARS-CoV-2 pneumonia patients.